GEO-Accumulation Index for Heavy Metals in Groundwater: a Study of Bompai and Sharada Industrial Estates, Kano Metropolis, Nigeria - Yalwa Rilwanu, Dr. Tasi'u; Yuguda Hassan, Fatima; Usman, Bishir; Rilwanu Yalwa, Ibrahim (Journal of Sustainable Natural Resources, 2022)
Abstract: The level of concentration of heavy metal in soil is detrimental to groundwater quality in Sharada and Bompai industrial areas. A total of 40 sampling points were selected from both two areas. The digested samples were analysed for As, Cd, Cr, Cu, Co, Ni and Pb using Inductively Coupled Plasma Atomic Emission Spectrometry (ICP-OES) machine. Geographic Information Systems (GIS) was used to model and present the spatiotemporal changes of the pollution sources and factors affecting the levels of pollution. Pollution in water and potential risks introduced by heavy metal accumulation were assessed using Geo-accumulation index. Results indicated that Cadmium and Arsenic are the most vulnerable around Bompai with mean of 0.2-0.4/mg/l and 1.3-1.6 mg/l respectively, Geo-accumulation index mapping showed that Arsenic, Cadmium and Copper to have high accumulation index ranging from strong to very strong (0.99-1.48), (0.01-0.22) and (0.27-0.33) respectively, Cobalt to have moderate contamination in Sharada (wet season) with (-0.39-0.12) while lead and Chromium has the least contamination index (uncontaminated). GIS modelling and mapping indicated that all the heavy metals were found in the groundwater of the two areas but among them Cd is more concentrated. South-western part of the study area confronts the most serious heavy metal pollution, hence the need for groundwater treatment before drinking to avoid dangers associated with heavy metals.